2022
DOI: 10.3390/ijms23179755
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of a Genome-Wide Association Study and a Transcriptome Analysis Reveals circRNAs as New Regulators Involved in the Response to Salt Stress in Maize

Abstract: Salinization seriously threatens the normal growth of maize, especially at the seedling stage. Recent studies have demonstrated that circular RNAs (circRNAs) play vital roles in the regulation of plant stress resistance. Here, we performed a genome-wide association study (GWAS) on the survival rate of 300 maize accessions under a salt stress treatment. A total of 5 trait-associated SNPs and 86 candidate genes were obtained by the GWAS. We performed RNA sequencing for 28 transcriptome libraries derived from 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…MiRNA plays a crucial role in responding to different stress conditions by regulating target genes [ 40 ]. miRNA was found to be involved in the response to salt stress in sorghum, sweet potato, maize, and rice [ 41 , 42 , 43 , 44 ]. The involvement of MiRNA has also been reported in the regulation of salt stress in wheat in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA plays a crucial role in responding to different stress conditions by regulating target genes [ 40 ]. miRNA was found to be involved in the response to salt stress in sorghum, sweet potato, maize, and rice [ 41 , 42 , 43 , 44 ]. The involvement of MiRNA has also been reported in the regulation of salt stress in wheat in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in maize, glycine betaine [ 34 , 35 ], trehalose [ 36 ], ascorbate–proline–glutathione [ 37 ], and phosphate [ 28 ], are applied to counter salt stress, which is favorable for the maintenance of Na + /K + balance and improvements in antioxidant defense. Recently, single or combined analyses of genomes [ 38 ], transcriptomes [ 34 , 39 ], proteomes [ 40 , 41 , 42 , 43 ], and metabolomes [ 44 , 45 ] and a genome-wide association study (GWAS) revealed differential expression genes, small RNAs, and regulatory networks in plants under salt stress [ 46 , 47 , 48 ], which provided valuable information to understand the mechanism of salt response.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that circular RNAs are involved in reprogramming the genomic function during adaptation to salt stress in maize [ 12 ]. It was also revealed that salt stress causes several epigenetic changes [ 13 ] including histone modifications [ 14 ], alterations of DNA methylation processes, and causes other epigenetic changes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%